Clinical Validation of Rapid Gout Detection Method and Kit - Amith Anugu; Rebecca Monastero; Sahana Pentyala; Vamiq M. Mustahsan; Yanming Cai; Jason Rosenfeld; David E. Komatsu; James Penna; Lawrence Hurst; Srinivas N. Pentyala (Methods and Protocols, 2021)
Gout is an inflammatory arthritis, which causes intense, acute pain due to the buildup of uric acid crystals in synovial fluid. The gold standard for gout diagnosis consists of synovial fluid analysis by polarized light microscopy, which is costly, time-intensive, and technique-dependent, therefore meriting a more efficient, inexpensive, and accessible method for diagnosis. We previously developed and validated a novel colorimetric gout detection method and device based on the reduction of silver nitrate by uric acid; here, we clinically validated our method and device using arthroscopically obtained synovial fluid samples from gout patients. We successfully identified uric acid crystals in clinical samples via our colorimetric method, visualized uric acid crystals in synovial fluid via handheld microscopy, and determined that silver nitrate stain did not interfere with the microscopic visualization of uric acid crystals necessary for diagnosis. We also developed and validated a method of processing turbid clinical samples for use in our device to prevent the obscuration of uric acid crystals by suspended material. Our method and device will clinically facilitate the immediate colorimetric diagnosis of gout and the subsequent bedside visualization of uric acid crystals in both ideal and turbid synovial fluid samples, allowing for a point-of-care diagnosis of gout.